1998
DOI: 10.1016/s0166-8641(97)00162-4
|View full text |Cite
|
Sign up to set email alerts
|

Self-homotopy equivalences which induce the identity on homology, cohomology or homotopy groups

Abstract: For a based, 1-connected, finite CW-complex X, we study the following subgroups of the group of homotopy classes of self homotopy equivalences of X: E * (X), the subgroup of homotopy classes which induce the identity on homology groups, E * (X), the subgroup of homotopy classes which induce the identity on cohomology groups and E dim+r # (X), the subgroup of homotopy classes which induce the identity on homotopy groups in dimensions ≤ dim X + r. We investigate these groups when X is a Moore space and when X is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 6 publications
0
22
0
Order By: Relevance
“…Let X be a Moore space M (G, n), for n ≥ 2 and G any infinite, finitely-generated abelian group with torsion. Then it follows from results of [AM98] that E * (X) = E * fg (X) In Corollary 4.6, we showed that for a 1-connected, finite-dimensional complex X, E * fg (X) is solvable. This raises the question of whether or not the group is nilpotent.…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…Let X be a Moore space M (G, n), for n ≥ 2 and G any infinite, finitely-generated abelian group with torsion. Then it follows from results of [AM98] that E * (X) = E * fg (X) In Corollary 4.6, we showed that for a 1-connected, finite-dimensional complex X, E * fg (X) is solvable. This raises the question of whether or not the group is nilpotent.…”
mentioning
confidence: 86%
“…This kind of example has been considered previously (cf. [AM98,Saw75]), but here we put it into the context discussed above.…”
Section: A Connection With the Gottlieb Groupmentioning
confidence: 99%
“…In this section, we review and summarize selected definitions and results provided in [1,3,5,12], knowledge of which would be useful when reading this paper.…”
Section: Preliminariesmentioning
confidence: 99%
“…Further, [3] also introduced the forms of the homomorphism induced by f on homotopy, homology, and cohomology groups, respectively. Now, we determine the form of the homomorphism induced by f on cohomotogy groups.…”
Section: This Definition Indicates That Ementioning
confidence: 99%
See 1 more Smart Citation